Naso-oropharyngeal microbiome from breast cancer patients diagnosed with COVID-19 - Viana, Maria Carolina; Curty, Gislaine; Furtado, Carolina; Singh, Bhavya; Bendall, Matthew L.; Viola, João P. B.; de Melo, Andreia Cristina; Soares, Marcelo A.; Moreira, Miguel A. M. (Frontiers in Microbiology, 2023)
Due to immunosuppressive cancer therapies, cancer patients diagnosed with COVID-19 have a higher chance of developing severe symptoms and present a higher mortality rate in comparison to the general population. Here we show a comparative analysis of the microbiome from naso-oropharyngeal samples of breast cancer patients with respect to SARS-CoV-2 status and identified bacteria associated with symptom severity. Total DNA of naso-oropharyngeal swabs from 74 women with or without breast cancer, positive or negative for SARS-CoV-2 were PCR-amplified for 16S-rDNA V3 and V4 regions and submitted to massive parallel sequencing. Sequencing data were analyzed with QIIME2 and taxonomic identification was performed using the q2-feature-classifier QIIME2 plugin, the Greengenes Database, and amplicon sequence variants (ASV) analysis. A total of 486 different bacteria were identified. No difference was found in taxa diversity between sample groups. Cluster analysis did not group the samples concerning SARS-CoV-2 status, breast cancer diagnosis, or symptom severity. Three taxa (Pseudomonas, Moraxella, and Klebsiella,) showed to beoverrepresented in women with breast cancer and positive for SARS-CoV-2 when compared to the other women groups, and five bacterial groups were associated with COVID-19 severity among breast cancer patients: Staphylococcus, Staphylococcus epidermidis, Scardovia, Parasegitibacter luogiensis, and Thermomonas.. The presence of Staphylococcus in COVID-19 breast cancer patients may possibly be a consequence of nosocomial infection.